2022
DOI: 10.33019/ijbe.v6i3.561
|View full text |Cite
|
Sign up to set email alerts
|

HUMAN CAPITAL DEVELOPMENT STRATEGY IN THE COVID-19 PANDEMIC ERA OF MSMEs IN PANGKALPINANG CITY

Abstract: As the backbone of the Indonesian economy, MSMEs continue to look for business models to achieve sustainable business performance. Human Capital is an essential factor in dealing with crises, where the Human Capital strategy consists of Knowledge, Competence, and Expertise. Therefore, the purpose of this study is to determine and analyze (1) the effect of Knowledge on Innovation, (2) the influence of Competencies on Innovation, (3) the influence of Innovation on Business Performance, and (4) the influence of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Human resource theory is important for MSMEs because it emphasizes the role of internal elements, such as knowledge, competence and expertise, in achieving sustainable business performance (Rokhman et al, 2023). It is very important for MSMEs to invest in developing employee knowledge and competencies to encourage innovation and improve business performance (Hamsani et al, 2022). Human resource management strategies, such as pay for performance and performance appraisals, can help MSMEs reward and retain talented employees (Mishra, 2014).…”
Section: Human Capital Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Human resource theory is important for MSMEs because it emphasizes the role of internal elements, such as knowledge, competence and expertise, in achieving sustainable business performance (Rokhman et al, 2023). It is very important for MSMEs to invest in developing employee knowledge and competencies to encourage innovation and improve business performance (Hamsani et al, 2022). Human resource management strategies, such as pay for performance and performance appraisals, can help MSMEs reward and retain talented employees (Mishra, 2014).…”
Section: Human Capital Theorymentioning
confidence: 99%
“…Several studies have shown that human resources, including knowledge, competence, expertise and leadership skills, have a positive impact on the success and performance of MSMEs. The impact of human resources on MSME performance shows that improving leadership skills can improve performance (Rokhman et al, 2023).The importance of human resources in MSMEs is because the knowledge and competencies they possess can influence innovation and business performance (Hamsani et al, 2022). Empowering small and medium enterprises (SMEs) through government policies, business capital support, and strengthening human resource capacity can encourage economic growth (Surya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Meningkatkan pengetahuan, kompetensi, dan keterampilan para pelaku UMKM sangat penting untuk mendorong inovasi dan meningkatkan kinerja bisnis (Hamsani et al, 2022;. UMKM harus berinvestasi dalam program pelatihan dan pengembangan keterampilan untuk membantu tenaga kerja mereka beradaptasi dengan era digital.…”
Section: Pendahuluanunclassified
“…UMKM harus berinvestasi dalam program pelatihan dan pengembangan keterampilan untuk membantu tenaga kerja mereka beradaptasi dengan era digital. UMKM harus fokus pada pengembangan produk, proses, dan strategi pemasaran baru agar tetap kompetitif di era digital (Hamsani et al, 2022). Inovasi dapat membantu bisnis membuat terobosan dan meningkatkan kinerja mereka secara keseluruhan.…”
Section: Pendahuluanunclassified